A survey of study participants' understanding of informed consent to participate in a randomised controlled trial of acupuncture. Issue 1 (December 2015) - Smith, Caroline; Fogarty, Sarah
Abstract Background It is important that potential study participants are appropriately informed and understand what is involved with their research participation. A few studies have examined study participants' understanding of the informed consent process and the adequacy of the information they received when agreeing to participate in a randomised controlled trial. Deficiencies in the consent process have been found. This topic remains an under researched area of acupuncture research. The aim of this study was to examine participants' understanding of their informed consent and the adequacy of the information presented when agreeing to participate in a randomised controlled trial of acupuncture. Methods All women who participated in a randomised controlled trial over an 11 month period were invited to participate in a survey. An anonymous self-completion questionnaire was designed and covered participants' understanding of informed consent in the clinical trial, their views of the information provided, the opportunity to ask questions, the use of sham acupuncture, their recall of study visits and processes for withdrawal, and their reason for participating in the trial. Results A response rate of 59 % was obtained. Over 90 % of subjects indicated there was plenty of opportunity to discuss the study prior to giving consent, and 89 % indicated that questions asked were answered to their satisfaction. The majority of women indicated the amount of information describing acupuncture was about right, however 24 % would have liked more. Information describing sham acupuncture was not considered adequate by 48 % of women, and 35 % would have liked more information, 30 % could not recall why, or were uncertain why a sham group was used. Participants indicated less understanding of the information relating to payment if they became ill due to study participation, risks and discomforts from the study interventions, which of the procedures were experimental and for how long they would be involved in the study. Conclusion Trial participants' understanding of informed consent was overall satisfactory but highlighted some areas of deficiency. Future studies could consider use of supplementary material such as Q and A fact sheets.